PENGARUH KECERDASAN EMOSIONAL DAN MINAT BELAJAR TERHADAP PEMAHAMAN AKUNTANSI (Studi Pada Mahasiswa Fakultas Ekonomi Universitas Nasional PASIM) - Sri Mulyeni; Dety Mulyanti (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The purpose of this study was to examine the effect of emotional intelligence and learning interest on the level of understanding of accounting. This study uses primary data which includes questions in the form of a questionnaire that is measured using a Likert scale. The research sample is 133 students who had completed introductory accounting courses. The results showed that emotional intelligence had an effect of 64,4% on students understanding of accounting and learning interest had an effect of 72,2% on students understanding of accounting, simultaneously emotional intelligence and student learning interest had a positive and significant impact on the level of accounting of faculty students economics study program of management and accounting at Pasim National University.